2018
DOI: 10.1590/0103-11042018s109
|View full text |Cite
|
Sign up to set email alerts
|

Núcleo de Apoio à Saúde da Família (Nasf): panorama nacional a partir de dados do PMAQ

Abstract: RESUMO O Núcleo de Apoio à Saúde da Família (Nasf) foi criado em 2008 visando aumentar a resolutividade e o escopo das ações da Atenção Básica (AB). Composto por uma equipe multiprofissional deve desenvolver atividades conjuntas com as equipes AB, seguindo a lógica do apoio matricial e das ações técnico-pedagógicas ou clínico-assistenciais, pretendendo a integralidade do cuidado. O objetivo deste estudo foi analisar o trabalho do Nasf no território brasileiro, considerando a integração entre as equipes Nasf e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
47

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 20 publications
0
15
0
47
Order By: Relevance
“…These results corroborate a previous study conducted using PMAQ Cycle II data, which concluded that infrastructure aspects were adequate for the work of the FHSU teams. 10 According to Donabedian, good structure conditions represent a favorable situation for a good work process, increase the likelihood of positive outcomes and, therefore, greater service ability to provide solutions to health problems. 6 As such, having knowledge of service characteristics is fundamental for health system planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results corroborate a previous study conducted using PMAQ Cycle II data, which concluded that infrastructure aspects were adequate for the work of the FHSU teams. 10 According to Donabedian, good structure conditions represent a favorable situation for a good work process, increase the likelihood of positive outcomes and, therefore, greater service ability to provide solutions to health problems. 6 As such, having knowledge of service characteristics is fundamental for health system planning.…”
Section: Discussionmentioning
confidence: 99%
“…PMAQ results reported by Bocardo et al also indicated the importance of greater development of initial training and continuing education in the context of the work of FHSU professionals. 10 Continuing education is equally important in view of the challenges faced by professionals in their actions, such as multiprofessional work, difficulties in creating and developing joint, intersectoral and integrated actions, so as to incorporate service user participation. 12 Results of a qualitative study involving FHSU professionals working in municipalities in Bahia state revealed that educational activities aimed at them were too scarce and insufficient to transform working practices.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the professional profile for comparison. With regard to training, a recent study (18) analyzed the work in Nasf in the Brazilian territory using data from the PMAQ and presented unsatisfactory data regarding specific training and continuing education, referred to as being offered by management for some or for no professionals by about 50% of the teams, which therefore requires professional initiative.…”
Section: Discussionmentioning
confidence: 99%
“…However, more than a decade after NASF was implemented, there are still challenges to be overcome for it to offer comprehensive health care. Particularly, there are difficulties related to the organization of the work processes and the low degree of integration with the other local and regional service networks [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%